Research Progress in Compositions, Contents and Functions of Oligosaccharides in Breast Milk and Cow’s Milk - ZHANG Zhuoxing, XU Huihui, LIU Ruwei, ZOU Yunxia, AN Qin, ZHANG Yali (Shipin Kexue)
Human milk oligosaccharides (HMOs), as the third largest solid component of breast milk, have been widely emphasized in recent years due to their important physiological functions. Bovine milk oligosaccharides (BMOs) have similar structures and functions to HMOs and similar complexity in composition, which make them high-quality ingredients in infant formula milk powder and functional foods. In this article, the structural compositions, quantitative distributions, physiological functions and industrial applications of HMOs and BMOs are reviewed to provide references for the research and development of HMOs and BMOs.